Review Pemilihan Adsorben Pada Proses Bleaching Dalam Metode Pemurnian Minyak Ikan - Cokorda Andi Janawi Tanaya; Ni Made Widi Astuti (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2022)
Bleaching is one of the processes in fish oil purification methods. In the bleaching process, it is necessary to use an adsorbent in the form of bleaching earth. This review article aims to review the various adsorbents that are most often used in fish oil purification methods. The review method in this article uses searches with search engines such as Google Scholar and Pubmed. Based on the search found below, there are several types of adsorbents that are most often used for the bleaching process in refining fish oil, namely Bentonite (Activated Charcoal), Magnesol XL, and Zeolite. Based on the three adsorbents found, each type has advantages and disadvantages which depend on the method used, temperature, speed and duration of centrifugation in the bleaching process.